PENGEMBANGAN KURIKULUM MULTIKULTURAL DI PERGURUAN TINGGI - Kapraja Sangadji (Pascasarjana IAIN Ambon, 2020)
The concept of multicultural education was born from a reflection in a group. The issues raised by multicultural education include: race, ethnicity, class, social, economic, gender, disability, age differences, and language. The emergence of these issues is no more a reflection of the condition of the people who experience inequality and injustice. This is defined as an educational process that gives equal opportunities to the entire nation regardless of treatment due to differences in ethnicity, culture and religion, which gives an appreciation of diversity, and which provides the same rights for ethnic minorities, in an effort to strengthen the unity, identity national and the nation's image in the eyes of the world. The above phenomenon is the study curriculum. Where the content of the curriculum itself in direct contact with all aspects of life and community issues. Reconstruction of multicultural education as a curriculum that reflects the four dimensions of curriculum development. Therefore education muliticutural not as hidden curriculum (hidden curriculum). Development and implementation of education multiculturalism in higher education, it can be packed into the curriculum such as education citizenship, the principles of multicultural education, educational foundation multicultural and Education Religiosity is done and can be done through a hidden curriculum or touch in the context of the development of noble character, has the intensity to foster and develop inter-religious harmony. By him, multicultural education can be included as a college curriculum in various subjects. Although the format of the higher.